2010
DOI: 10.1111/j.1439-0310.1965.tb01496.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexuelle Prägung bei Anatiden2,3

Abstract: Inhalt: I. Zur Klärung des Begriffs S. 50. — II. Was ist bis jetzt über Sexualprägung bekannt? S. 53. — III. Methode S. 54. — IV. Paarbildung und Paarverhalten, besonders bei der Stockente S. 57. — V. Prägungsversuche mit Stockenten — ♂♂, Kontrollen S. 58, Erörterung S. 59. — VI. Prägungsversuche mit Stockenten — ♀♀ S. 61. — VII. Prägung durch Mutter und Geschwister S. 63. — VIII. Wann finden die entscheidenden Eindrücke statt? S. 64. — IX. Wie lange bleibt die Prägung erhalten? S. 67. — X. Prägung von Stocker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(29 citation statements)
references
References 34 publications
(4 reference statements)
1
27
0
1
Order By: Relevance
“…However, differences between intraspecific and interspecific imprinting experience could be of great importance. Differences in the experimental design could perhaps also account for the different results between SCHUTZ (1965) and the present study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, differences between intraspecific and interspecific imprinting experience could be of great importance. Differences in the experimental design could perhaps also account for the different results between SCHUTZ (1965) and the present study.…”
Section: Discussionmentioning
confidence: 69%
“…Is it dependent on a more or less closed program (MAYR 1974;SCHUTZ 1965;KLINT 1975)? Since there are no differences between 8 8 and 99 (in Table 1) and the pair formation process can be either male or female dominated, this point will not be considered in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…SCHUTZ , 1975KLINT 1975;WALTER 1973). SCHUTZ (1965) suggests that female ducks recognize male conspecifics through a genetic mechanism. Such a mechanism seems plausible when the high inter-specific variability in plumage coloration of male ducks is considered.…”
Section: 3mentioning
confidence: 99%
“…Thus, each brood included an 'experimental' male reared with heterospecific females and a 'control' male reared with females of his own species. It was not possible to form larger broods or rear ducklings with adult females owing to logistical constraints, but previous work has demonstrated that interaction with siblings contributes to both filial (Lickliter & Gottlieb 1986) and sexual (Schuetz 1965;Cheng et al 1978) imprinting in Anas ducklings. Broods were reared in visual isolation in outdoor enclosures with ad libitum access to food, water and shelter.…”
Section: Methodsmentioning
confidence: 99%